Designing of KB (Family Planning) Service Information System in Pratama Clinic Salatiga - Penidas Fiodinggo Tanaem; Agustinus Fritz Wijaya; Fransiska Wahyuning Kurniawati; Resa Saputri (SISFORMA, 2020)
The writing of this Journal aims to explain the design of the KB service information system that is available at the Pratama Clinic Salatiga. As for the background of making this journal because Indonesia is one of the countries that has the largest population in the world and this happens because the number of births in Indonesia that cannot be controlled. Although the government has launched a KB that is applied by using contraceptives, it has not been able to overcome the problems that occur. The number of uncontrolled births is due to the large number of families who complain about the use of contraceptives. Expensive, difficult to obtain and uncomfortable when used is an excuse for those who do not want to use contraception so that the number of births cannot be controlled, besides that along with the development of existing KB services it is increasingly ignored because people prefer things that are practical and do not like to follow complicated programs or services such as family planning services so that it causes more and more people who are lazy to attend family planning and have an impact on increasing numbers birth. Seeing from the phenomena above, the thought is formed that service information systems are really needed in the current era of development, especially to facilitate all the work that cannot be done in a short time. So from this the special information system design was made in the field of family planning services in the Pratama Clinic in the form of a journal. In this journal, it explains about how a family planning service can be accessed easily without wasting too much time so that the public wants to participate in the family planning service. One way that can be done is to establish an information system that can be used for family planning services with a system that is easily understood and accessed by the general public.